2015
DOI: 10.1097/qad.0000000000000671
|View full text |Cite
|
Sign up to set email alerts
|

Increasing HIV serostatus disclosure in low and middle-income countries

Abstract: Objective To review the effectiveness of interventions to increase HIV serostatus disclosure in low- and middle-income countries. Design Systematic review of peer-reviewed articles providing pre-post or multi-arm evaluations of disclosure interventions, defined broadly as any intervention with the goal of increasing rates of voluntary disclosure of HIV serostatus through self-disclosure or partner notification. Methods Articles were included if they reported post-intervention evaluation results and were pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…cognitive-behavioral support groups, community-based/ home-based outreach services, and partner-notification services [42]. The actions and behavioral targets of support group interventions ranged from (i) information transfer and motivational interviewing to improve patient activation, (ii) experience-sharing and communication skills development to facilitate comfort with disclosure, and (iii) development of planning and conflict resolution skills to strengthen coping behaviors.…”
Section: Interventions To Promote Social Normalizationmentioning
confidence: 99%
“…cognitive-behavioral support groups, community-based/ home-based outreach services, and partner-notification services [42]. The actions and behavioral targets of support group interventions ranged from (i) information transfer and motivational interviewing to improve patient activation, (ii) experience-sharing and communication skills development to facilitate comfort with disclosure, and (iii) development of planning and conflict resolution skills to strengthen coping behaviors.…”
Section: Interventions To Promote Social Normalizationmentioning
confidence: 99%
“…Maternal HIV disclosure has generally been found to be beneficial for children, parents and families (Qiao et al., 2013) and became a World Health Organization recommendation in 2012 (WHO, 2011). However, there is a dearth of interventions to support parents (Kennedy et al., 2015), in particular those with younger children, with this challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…We hope that these studies, conducted in five different countries, will assist in moving the field forward towards more effective interventions for both paediatric and parental HIV status disclosure. As reported by Kennedy et al [32], only few interventions to date have been robustly tested in LMIC that were intended to support either paediatric or parental HIV status disclosure. Of the 13 disclosure intervention studies they identified, only one was concerned with disclosure to children, focusing in particular on maternal HIV status disclosure to HIV-uninfected children [32].…”
mentioning
confidence: 99%